PENENTUAN UKURAN OPTIMUM MATERIAL DENGAN METODE REGRESI LINEAR GANDA UNTUK MENINGKATKAN EFISIENSI MATERIAL PT TMMIN â STAMPING PLANT - Trihandika, Trihandika; Abbas, Bahtiar Saleh (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
Material efficiency from part weight comparation to material weight in PT TMMIN for stamping material body of A Model car is still low. This condition influences the high of production cost. That is why a method to determine an optimum material measurement, mhich is material measure that is able to fulfil the part without reducing the quality is needed. Data collection,information, and a test with supportive data is done to get analysis method to produce a formula in determining a material optimum measurement. From the formula, it can become a guide to material measurement for stamping material body of A Model car so it can increase efficiency and cost reduction.